2021
DOI: 10.3389/fpsyg.2021.686914
|View full text |Cite
|
Sign up to set email alerts
|

The Simple View of Reading in Children Acquiring a Regular Orthography (Italian): A Network Analysis Approach

Abstract: In the present study, we explored the unique contribution of reading accuracy, reading fluency and linguistic comprehension within the frame of Simple View of Reading (SVR). The experimental sample included 118 3rd to 5th grade children learning Italian, a language with a highly regular orthography. We adopted a flexible method of analysis, i.e., the Network Analysis (NA), particularly suited for exploring relations among different domains and where the direct relations between a set of intercorrelated variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Although not focused on any specific IQ battery or comprehensive intelligence theory, studies with select sets of cognitive and or achievement tests have demonstrated how PNA descriptive models can provide support for potential causal mechanisms or theories of cognitive deficits in first episode psychosis ( Sánchez-Torres et al 2022 ), the Simple View of Reading model (SVR; Angelelli et al 2021 ), a multi-level model of learning skills ( Zoccolotti et al 2021 ), and the age-differentiated relations between cognitive efficiency abilities (i.e., inhibition, working memory, fluid intelligence, and speeded attention) ( Neubeck et al 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not focused on any specific IQ battery or comprehensive intelligence theory, studies with select sets of cognitive and or achievement tests have demonstrated how PNA descriptive models can provide support for potential causal mechanisms or theories of cognitive deficits in first episode psychosis ( Sánchez-Torres et al 2022 ), the Simple View of Reading model (SVR; Angelelli et al 2021 ), a multi-level model of learning skills ( Zoccolotti et al 2021 ), and the age-differentiated relations between cognitive efficiency abilities (i.e., inhibition, working memory, fluid intelligence, and speeded attention) ( Neubeck et al 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important next step would be a network analysis of cognitive and achievement domains linked to theory (e.g., see Angelelli et al 2021 ; Zoccolotti et al 2021 ). We are currently unfamiliar with methodological options for exploring relations between a set of network predictor measures (cognitive) with a set of network outcome measures (achievement) in the same network, or linked sets of networks.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Atheoretical, data-driven, and descriptive PNA models can illuminate previously hidden insights by examining high-dimensional data where tests can concurrently serve as both predictor and predicted variables ( Angelelli et al 2021 ; Epskamp et al 2017 ). Briefly, in PNA, the manifest measures (tests) are represented as nodes .…”
Section: In Search Of Cognitive and Achievement Causal Mechanisms: A ...mentioning
confidence: 99%
“…The benefits of PNA (over common cause factor models) are multiple ( Angelelli et al 2021 ; Borsboom et al 2021 ; Epskamp et al 2017 ; McGrew et al 2023 ). In the current context, “the primary value of these descriptive models is their ability to function as a bridge to theory formation and the ability to hypothesize, and empirically test or statistically simulate, potential causal mechanisms in the network ( Borsboom et al 2021 ; Haslbeck et al 2021 )” ( McGrew et al 2023, p. 5 ).…”
Section: In Search Of Cognitive and Achievement Causal Mechanisms: A ...mentioning
confidence: 99%
“…The disorders studied with these methods include adult and paediatric epilepsies (Garcia-Ramos et al, 2021Kellermann et al, 2016Kellermann et al, , 2015, mild cognitive impairment (Ferguson for the Alzheimer's Disease Neuroimaging Initiative, 2021), Alzheimer's disease (Ferguson for the Alzheimer's Disease Neuroimaging Initiative, 2021; Nevado et al, 2021a;Tosi et al, 2020;Wright et al, 2021), vascular encephalopathy (Tosi et al, 2020), stroke (Massa et al, 2015), and frontal and non-frontal lesions arising from various aetiologies (Jonker et al, 2019). Comparable studies have created network models of more specific aspects of cognition, including intelligence (Kan et al, 2019;Schmank et al, 2019;van der Maas et al, 2017), reading (Angelelli et al, 2021;Goring et al, 2021;Zoccolotti et al, 2021), and semantic fluency (Bertola et al, 2014;De Marco et al, 2021;Goni et al, 2011˜ ;Lerner et al, 2009;Nevado et al, 2021b), or developmental processes like ageing (Garcia-Cabello et al, 2021;Konigs et al, 2021¨ ), in clinical and non-clinical groups. Other related studies have combined neuroimaging and cognitive, behavioural, and/or self-report data in clinical groups (Bathelt et al, 2020;Hilland et al, 2020;Simpson-Kent et al, 2021), or investigated relationships amongst neuropsychological variables and the symptoms of autism spectrum disorder (Ibrahim et al, 2016) and attention deficit hyperactivity disorder (Eadeh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%